Future Scenarios - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The Future Scenarios initiative works in a participatory and interactive way with technical advisors and other key stakeholders in East and West Africa to build some up pictures of different worlds, or narratives, that identify the uncertainties that policy-makers may be faced with at the regional level. The idea is to help decision makers start analysing the transformational changes that will be needed in terms of policies, institutions and governance in agricultural production and food security over the next 15 years. The narratives identify a range of possible pro-active and re-active positions to be taken for a number of different “futures”.